Marketing strategy process: Quantitative analysis of the customers’ satisfaction - Dudzevičiūtė, Gitana; Peleckienė, Valentina (Business: Theory and Practice, 2010)
Several years ago one of the most respected management-consulting firms, McKimsey & Co., defined the key business practices that characterized “well-run organizations”. The results of this study were summarized and the most fundamental conclusion was made that the most successful companies are not more successful because of any superiority in strategic planning (Schoell et al. 1987). It is impossible to determine whether a strategy was correct or not if the implementation of this strategy is unsound. The implementation of the marketing strategy is effective and the strategy is appropriate if the targets of the company met requirements for growth, share and profits (Grundey 2008). The most important factor indicating the success of the marketing strategy is the customers’ value creation by meeting their needs (Alvin J. Silk 2006). The problem exists how to evaluate and calculate in a quantitative manner the customers’ satisfaction factor. The additional efforts and resources are necessary (Minnesota Dep. 2008). The aim of this paper is to describe and to make a comparative analysis of the marketing strategy processes proposed by different authors, to make quantitative analysis of the customers’ satisfaction, referring to the particular example of the company.